INFLUENCE OF COST LEADERSHIP PROCUREMENT STRATEGY ON PERFORMANCE OF MANUFACTURING FIRMS IN KENYA - Kiprotich, Evans; Gachunga, Dr. Hazel; Bonuke, Ronald (European Journal of Business and Strategic Management, 2018)
Purpose: The study aims at providing insights on procurement competitive strategies used by manufacturing firms in Kenya to achieve competitiveness and increase their performance. Methodology: The study will adopt the explanatory research design. The study targeted population of 766 procurement managers from manufacturing firms in Kenya. The Yamane's formula was used to compute a sample size of 264 procurement managers. Stratified, simple random and purposive sampling was used to select respondents. Questionnaire was used to collect primary data. Content validity of the instrument was determined by the researcher using expert judgment. Cronbach's Coefficient Alpha will be used to determine the reliability of the research instrument. The data was coded and entered in the computer for analysis using the Statistical Package for Social Sciences. Pearson Correlation Coefficient was used to determine relationship between cost leadership procurement strategies and firm performance. Results: The study findings depicted that there was a significant positive relationship between cost leadership and performance of manufacturing firms (r=0.245, p-value=0.00). From the regression model, (R2 = .053) shows that cost leadership account for 5.3% variation in performance of manufacturing firms. There was a positive significant relationship between cost leadership and performance of manufacturing firms (Î²=0.231 and p value<0.05). Unique contribution to theory, practice and policy: The researcher recommends that the manufacturing firms should adopt cost leadership procurement strategy. The manufacturing firms pay attention to cheap sources of raw materials and other value chain management practices that result in reduction of cost. Keyword: Cost leadership, procurement strategy, performance, manufacturing firms, Kenya